Study on Food Habits of Moustached Thryssa (Thryssa Mystax) at Ujung Pangkah Waters, East Java - Sulistiono Sulistiono; Fifit Maulani; Murniarti Brodjo; Charles PH Simanjuntak (Jurnal ILMU DASAR, 2010)
Moustached thryssa is one of an important fishery commodity in ujung pangkah waters. The study aimed toinvestigate food habits of the fish caught in the area. This study was conducted in ujung pangkah waters, gresik,east java using fish samples (n=76 males, n=119 females) collected during january to june 2006. Research resultshows that shrimps was a main food, bivalva and parts of crustacean were complementary food, while copepodsand pollychaeta were suplementary food both for male and female fish. Based on index of stomach contents, theindex was higher during january and april for male and female fish. Percentage of food of the fish variedaccording to size. According to simmilariy index, the main food of male and female fish was simmilar.